DETERMINAN PENYAKIT BERBASIS LINGKUNGAN PADA ANAK BALITA DI INDONESIA - Restu Prasetyo; Tiodora Hadumaon Siagian (Research Centre for Population, Indonesian Institute of Sciences, 2017)
Nowadays, many health problems are caused by unhealthy lifestyle and neighborhood conditions. This situation can be seen from a substantial contribution of environmental diseases, such as Acute Respiratory Infection (ARI) and diarrhea, to the morbidity and mortality of children under age five in Indonesia. In line with this problem, this study aimed to find out general description and determinants of environmentally based diseases in Indonesia by utilizing multinominal logistic regression method. This study used the 2013 Riset Kesehatan Dasar (Riskesdas). The result of the research showed that more than one-third of children under-five in Indonesia had suffered ARI disease and 1 of every 25 of them had suffered diarrhea. This study also found that similarities between morbidity determinants of ARI and diarrhea, such as slum dwelling, mothers education level, mother’s behavior in washing hands with soap when their hands are dirty, mother’s behavior in washing hands after they have defecated, as well as sex and age of the children under-five. Moreover, mother’s education level was the highest contributor amongst the determinants of morbidity of ARI and diarrhea in children under five. It is recommended that the government can further improve the education of women to increase women's knowledge about the healthcare environment and healthy behavior.